2016
DOI: 10.9787/pbb.2016.4.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Yielding Rice Varieties Suitable for Swampy Lands in Indonesia

Abstract: Productivity of swampy land rice varieties in Indonesia remains low due to abiotic and biotic stresses. Iron toxicity, submergence and long-term flooding are common problems that affect plant growth, sometimes leading to total crop loss. Meanwhile, rice blast, rice tungro virus (RTV), and bacterial leaf blight (BLB) can also lead to severe yield loss. These stresses could be overcome by an integrative approach of cultural practices and planting multi-stress tolerant rice. Here we describe the development of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
1
6
0
4
Order By: Relevance
“…We found that moderate tolerant variety, Inpara 8 had best grain yield and agronomic performance under excess iron compared to the tolerant variety, Cilamaya Muncul (Figure 3). This can be explained that Inpara 8 had been designed for targeted in swampy agroecological zone, where iron toxicity is main problem (Zarwazi et al 2016;Rumanti et al 2016). This finding is also strengthen our experience that cultivating Inpara 8 in iron hot spot farm of swampy area in South Sumatera also showed mild reaction of leaf bronzing.…”
Section: Cilamaya Munculsupporting
confidence: 76%
“…We found that moderate tolerant variety, Inpara 8 had best grain yield and agronomic performance under excess iron compared to the tolerant variety, Cilamaya Muncul (Figure 3). This can be explained that Inpara 8 had been designed for targeted in swampy agroecological zone, where iron toxicity is main problem (Zarwazi et al 2016;Rumanti et al 2016). This finding is also strengthen our experience that cultivating Inpara 8 in iron hot spot farm of swampy area in South Sumatera also showed mild reaction of leaf bronzing.…”
Section: Cilamaya Munculsupporting
confidence: 76%
“…Inpara 8, a high-yielding rice cultivar is widely cultivated and grows well in tidal swamp of South Sumatra [15]. Inpara 8 derived from a double cross of Cinglonik/IRBB7//Memberamo/IR64 [9] was used as Sub1 donor parent for submergence tolerance. In our previous study [14], the recipient parent Inpago 5 showed drought tolerance in generative phase and high-yield under non-tidal cultivation.…”
Section: Plant Materials and Crossing Schemementioning
confidence: 99%
“…Sub1A, Sub1B, Sub1C, but only Sub1A gene was found in submerged tolerant cultivar, FR13A. Inpara 8 has the Sub1A gene inherited by FR13A [9]. Sub1A will slackens the ethylene production and GA responsiveness during submerged condition, maintains carbohydrate reserves, and significantly elongates endurance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Keempat genotipe tersebut . Keempat genotipe tersebut memiliki toleransi terhadap cekaman rendaman, yang dikendalikan oleh gen Sub1 yang terekpresi saat tercekam rendaman (Rumanti et al, 2016) dan genangan hingga 60 cm (Sitaresmi et al, 2019). Peng 2017 (Sasmita et al, 2019;Ningsih, 2011).…”
Section: Keragaan Komponen Hasil Dan Bobot Panen Galur Dan Varietasunclassified